The antenna-like domain of the cyanobacterial ferrochelatase can bind chlorophyll and carotenoids in an energy-dissipative configuration - Pazderník, Marek; Mareš, Jan; Pilný, Jan; Sobotka, Roman (The Journal of biological chemistry, 2019)
Ferrochelatase (FeCh) is an essential enzyme catalyzing the synthesis of heme. Interestingly, in cyanobacteria, algae, and plants, FeCh possesses a conserved transmembrane chlorophyll a/b binding (CAB) domain that resembles the first and the third helix of light-harvesting complexes, including a chlorophyll-binding motif. Whether the FeCh CAB domain also binds chlorophyll is unknown. Here, using biochemical and radiolabeled precursor experiments, we found that partially inhibited activity of FeCh in the cyanobacterium Synechocystis PCC 6803 leads to overproduction of chlorophyll molecules that accumulate in the thylakoid membrane and, together with carotenoids, bind to FeCh. We observed that pigments bound to purified FeCh are organized in an energy-dissipative conformation and further show that FeCh can exist in vivo as a monomer or a dimer depending on its own activity. However, pigmented FeCh was purified exclusively as a dimer. Separately expressed and purified FeCH CAB domain contained a pigment composition similar to that of full-length FeCh and retained its quenching properties. Phylogenetic analysis suggested that the CAB domain was acquired by a fusion between FeCh and a single-helix, high light-inducible protein early in the evolution of cyanobacteria. Following this fusion, the FeCh CAB domain with a functional chlorophyll-binding motif was retained in all currently known cyanobacterial genomes except for a single lineage of endosymbiotic cyanobacteria. Our findings indicate that FeCh from Synechocystis exists mostly as a pigment-free monomer in cells but can dimerize, in which case its CAB domain creates a functional pigment-binding segment organized in an energy-dissipating configuration.
Keywords: Synechocystis; ferrochelatase; vazebná místa; pigment binding; carotenoid; chlorofyl a; fylogeneze; light harvesting complex (LHC)-like proteins; Phylogeny; Chlorophyll; chlorophyll; plant biochemistry; heme; Chlorophyll A; photosynthesis; membrane protein; ferrochelatasa; Ferrochelatase; chlorofyl; Binding Sites; Light-Harvesting Protein Complexes; Carotenoids; konformace proteinů; dimerizace; Dimerization; Protein Conformation; chloroplast; světlosběrné proteinové komplexy; photosynthetic pigment; karotenoidy